If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -1pq + -4pr = 0 Solving 5p + -1pq + -4pr = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'p'. p(5 + -1q + -4r) = 0Subproblem 1
Set the factor 'p' equal to zero and attempt to solve: Simplifying p = 0 Solving p = 0 Move all terms containing p to the left, all other terms to the right. Simplifying p = 0Subproblem 2
Set the factor '(5 + -1q + -4r)' equal to zero and attempt to solve: Simplifying 5 + -1q + -4r = 0 Solving 5 + -1q + -4r = 0 Move all terms containing p to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -1q + -5 + -4r = 0 + -5 Reorder the terms: 5 + -5 + -1q + -4r = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1q + -4r = 0 + -5 -1q + -4r = 0 + -5 Combine like terms: 0 + -5 = -5 -1q + -4r = -5 Add 'q' to each side of the equation. -1q + q + -4r = -5 + q Combine like terms: -1q + q = 0 0 + -4r = -5 + q -4r = -5 + q Add '4r' to each side of the equation. -4r + 4r = -5 + q + 4r Combine like terms: -4r + 4r = 0 0 = -5 + q + 4r Simplifying 0 = -5 + q + 4r The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
p = {0}
| 5x(-4x+2)=13x+9 | | 0.09x+0.1=0.5(x-12) | | X+7=.5x+12 | | 282*3= | | 8x-6-x+1=67-2x | | -6-v=-12 | | Y=14.95+.13x+.39x-15 | | -2(10+x)=26 | | 6x-7y=4 | | 189=-9(-4+x) | | 4(5x+1)=8(3x-5) | | 6+.10x=.15x | | 2.25=m(8)+b | | lnx=.34 | | x^2+4x-957=0 | | 6(r+4)-5(1+4r)= | | 4x+9=5x-11 | | 7(4+y)=-14 | | -6(3+y)=-12 | | ln(4x)= | | x+24=4x-30 | | 0=5(r^2+4)-30r | | 2(r-4)=4r | | x(x+2)(x+4)=105 | | n+2=-4 | | x(x-2)(x+4)=105 | | 2x+6x+6=10 | | 3ab+5cd+6ab= | | 23-2x+-5=-6 | | f(t)=4r-10 | | x^2-21x+6=5x+6 | | 4a^2+4ab+b^2=0 |